What Measure of Inflation Should a Developing Country Central Bank Target? - Rahul Anand; Eswar Prasad; Boyang Zhang (Institute for the Study of Labor (IZA), 2015)
In closed or open economy models with complete markets, targeting core inflation enables monetary policy to maximize welfare by replicating the flexible price equilibrium. We analyze this result in the context of developing economies, where a large proportion of households are credit constrained and the share of food expenditures in total consumption expenditures is high. We develop an open economy model with incomplete financial markets to show that headline inflation targeting improves welfare outcomes. We also compute the optimal price index, which includes a positive weight on food prices but, unlike headline inflation, assigns zero weight to import prices.
Keywords: E31; E52; E61; 330; headline inflation; core inflation; monetary policy framework; inflation targeting; financial frictions